The Effect of Interest Rates, Economic Growth, and Inflation on The Money Supply - Hamzah; Fatmawati; Fitrianti, Retno (Economics and Business Journal (ECBIS), 2023)
Money plays a strategic role in economics and was often initially interpreted as a widely accepted means of payment, especially due to its primary function as a medium of transaction. The purpose of this study is to analyze the effects of interest rates, economic growth and inflation on the money supply. The variables observed in this study are the floating money in circulation (M1) as the dependent variable and interest rates, economic growth and inflation as the independent variables. The study uses secondary data from his 2013 to his 2022 from the Central Bureau of Statistics. This study uses multiple regression analysis with the SPSS program. The results of this study demonstrate that the independent variables (interest rates, GDP, and inflation) simultaneously affect the dependent variable (money supply). On the other hand, only interest rate variables affect the money supply, while GDP and inflation variables do not.